The Influence Of Brand Image, Word Of Mouth And Brand Trust On The Decision To Choose A School Through Choosing Interest At Ira School Foundation Medan - Vanindah, Jeihan; Tambunan, Sari Bulan; Suryani, Wan (UNIVED Press, 2026)
This study aims to determine the influence of Brand Image, Word of Mouth, and Brand Trust on the Decision to Choose a school at Yayasan Perguruan IRA in Medan City, with Interest in Choosing as an intervening variable. This quantitative research employs the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using the SmartPLS 3 application to examine both direct and indirect relationships among Brand Image, Word of Mouth, Brand Trust, Interest in Choosing, and Decision to Choose. The study utilizes primary data collected through research questionnaires. Respondents consist of parents, teachers, and students of Yayasan Perguruan IRA Medan, totaling 100 participants. The hypothesis testing results indicate that Brand Image, Word of Mouth, and Brand Trust have a positive direct influence on the Decision to Choose. Interest in Choosing also has a positive influence on the Decision to Choose. Indirectly, Brand Image, Word of Mouth, and Brand Trust exert a positive effect on the Decision to Choose through Interest in Choosing.